THE CORRELATION BETWEEN KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN WITH TETANUS DIPHTERIA IMMUNIZATION TO PREGNANT WOMEN IN BANDAR SETIA VILLAGE - Lasria Simamora; Riska Susanti Pasaribu; Henny Rista; Deby Cintya Yun (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
One of the causes of maternal death is infection. Tetanus infection caused by the bacterium Clostridium tetani is one of the causes of maternal and infant mortality. The author aims to conduct research on the relationship between knowledge and attitudes of pregnant women with tetanus diphtheria immunization in the village of Bandar Setia, Deli Serdang Regency. This was a descriptive study with a cross sectional approach. The population was pregnant women recorded at the Bandar Setia Polindes in January - March 2023 totaling 34 people. The sampling technique in this study was the total sampling technique because the total population was less than 100 people. The time of the study was January - March 2023. The data collection technique was primary data by filling out a questionnaire. Questionnaires are used to measure the knowledge and attitudes of pregnant women, while secondary data is obtained from the register of pregnant women who come to check their pregnancies. Data analysis included Univariate and Bivariate with the chi square test. The test was carried out to determine the significance test using a 95% confidence level and an error rate (α) = 5%. The results of the chi square statistical test on the knowledge variable, the value of p = 0.003 (p <0.05) this shows that knowledge has a significant relationship with the administration of Td immunization, as well as on the attitude variable the results of the chi square statistical test obtained a value of p = 0.001 (< 0.05) this shows that attitude has a significant relationship with giving Td immunization to pregnant women. It is hoped that health workers will promote more promotion of Tanus Diphtheria Immunization for women of childbearing age, especially pregnant women, to increase the knowledge of women of childbearing age about Tetanus Diphtheria immunization.